(untitled) (Scientific journal of the Fergana State University, 2024)
The article discusses the historical and etymological analysis of the ethnotoponyms Bagish, Karabagish, Chongbagish, Sarbagish, Kokbagish, Chbagish, Arbagish based on the connecting component. As a result of our research and observations based on sources given in the scientific literature, the features of ethnotoponyms in terms of naming were analyzed in order to study the names of clans and tribes embedded in the ethnic composition of the Uzbek people, as well as toponyms. which were formed on the basis of these names in individual regions. At the same time, they relied on scientific observations and methods devoted to issues of toponymy, onomastics, linguogeography, areal linguistics, nomenology in Turkology and Uzbek linguistics. In the course of research, it was proven that the toponym Bagish was used as a family name and the toponym as a totem. At the end of the article, it can be concluded that the lexeme Bagish has moved into the name of the clan and has taken its place as a “totem” expressing the meaning of deer or deer, Chongbagish means most of the Bagish clan, sari(q) bagish means to know or rich wealth belonging to the Bagish clan , Karabagish and Kokbagish, it was concluded that the ethnonyms in their meaning expressed the location of the clans.